SOCIO-ECONOMIC DETERMINANTS OF HOME BASED AND OUTDOOR WOMEN WORKERS IN PAKISTAN - Ayesha Rashid; Khawaja Asif Mehmood; Muhammad Zahir Faridi (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper analyzes the influence of socio-economic factors on women’s decision to participate in economic activities as home based or outdoor worker. For empirical analysis, cross-sectional data is collected from 1227 working women from Multan Division, Pakistan. The binary logistic regression model is used and results concluded that the probability of opting home based work decreases with an additional year of education. Various factors such as; age, presence of disease, head of household, household size, children under age 5 years, domestic responsibilities, restrictions to achieve education, self-employment, work less than 35 hours per week, worker satisfaction, ownership of assets, and distance from home to district headquarter are positively related with women participation decision to be home based worker. While factors like; number of dependents, children aged 5-15 years, outside work permission, working as employee, work more than 34 hours per week, cooperative attitude, labor laws, urban location, and joint family setup have negatively influenced the women decision to work from home. The results suggest that human capital should be on top priority by allotting extra resources for education, health and vocational trainings to improve the decent work opportunities for home-based workers for the development of Pakistan.